PSYCHOLOGICAL CHARACTERISTICS OF BEHAVIOR CONTROL IN ADOLESCENT PERIOD - Abdugadirova Mukhtasarkhan Latibjan's daughter (Web of Journals Publishing, 2024)
The article reveals the psychological characteristics of the manifestation of self-control in adolescence. First of all, the analysis of opinions about the content of the concept of self-management, self-management in educational activities is presented. In particular, the levels of manifestation of self-control in behavior during adolescence have been studied on the basis of empirical studies.
Keywords: adolescence, self-regulation, behavior, planning, modeling, programming, outcome evaluation, flexibility, independence, general level of self-regulation.